A comparison of how deep brain stimulation in two targets with anti-compulsive efficacy modulates brain activity using fMRI in awake rats. (April 2023) - Derksen, Maik; Zuidinga, Birte; van der Veer, Marijke; Rhemrev, Valerie; Jolink, Linda; Reneman, Liesbeth; Nederveen, Aart; Forstmann, Birte; Feenstra, Matthijs; Willuhn, Ingo; Denys, Damiaan
Highlights: A novel, custom-made setup that enables DBS with simultaneous fMRI-acquisition in awake rodents. Differential and overlapping effects of DBS in ventromedial striatum (VMS) and internal capsule (IC). DBS in both IC and VMS activates the IC area. DBS in the rostral IC leads to increased cross-correlation between the IC area and OFC and nucleus accumbens, whereas DBS in VMS does not affect cross-correlations. Rodent fMRI is a promising approach to elucidate the mechanisms of action of DBS. Abstract: Deep brain stimulation (DBS) is an established neuromodulatory intervention against otherwise treatment-refractory obsessive-compulsive disorder (OCD). Several DBS targets, all of which are part of brain networks connecting basal ganglia and prefrontal cortex, alleviate OCD symptoms. Stimulation of these targets is thought to unfold its therapeutic effect by modulation of network activity through internal capsule (IC) connections. Research into DBS-induced network changes and the nature of IC-related effects of DBS in OCD is needed to further improve DBS. Here, we studied the effects of DBS at the ventral medial striatum (VMS) and IC on blood-oxygen level dependent (BOLD) responses in awake rats using functional magnetic resonance imaging (fMRI). BOLD-signal intensity was measured in five regions of interest (ROIs): medial and orbital prefrontal cortex, nucleus accumbens (NAc), IC area, and mediodorsal thalamus. In previous rodent studies, stimulation at both target locations resulted in a reduction of OCD-like behavior and activation of prefrontal cortical areas. Therefore, we hypothesized that stimulation at both targets would result in partially overlapping BOLD responses. Both differential and overlapping activity between VMS and IC stimulation was found. Stimulating the caudal part of the IC resulted in activation around the electrode, while stimulating the rostral part of the IC resulted in increased cross-correlations between the IC area, orbitofrontal cortex, and NAc. Stimulation of the dorsal part of the VMS resulted in increased activity in the IC area, suggesting this area is activated during both VMS and IC stimulation. This activation is also indicative of VMS-DBS impacting corticofugal fibers running through the medial caudate into the anterior IC, and both VMS and IC DBS might act on these fibers to induce OCD-reducing effects. These results show that rodent fMRI with simultaneous electrode stimulation is a promising approach to study the neural mechanisms of DBS. Comparing the effects of DBS in different target areas has the potential to improve our understanding of the neuromodulatory changes that take place across various networks and connections in the brain. Performing this research in animal disease models will lead to translational insights in the mechanisms underlying DBS, and can aid improvement and optimization of DBS in patient populations.